Long-term simulation model for a knowledge-based economy - Welfe, Władysław (Uniwersytet Ekonomiczny we Wrocławiu, 2010)
Development of market economies towards the economies based on knowledge impliesthe construction of new long-term macroeconometric models. The structure of the new longterm W8D model for Poland is presented. Being a complete model, it covers the blocks ofequations explaining final demand and the production process as well as financial flows. Theequations explain both the long-term relationships and the dynamic adjustments using ECM.The model is of medium-size, including 235 equations, of which 111 are stochastic. They aremostly non-linear, dynamic and compose a simulations system.The consumption and investment function estimates are shown. The paper discusses thenotions of extended production function and total factor productivity (TFP). The TFPrepresents the impacts of new technologies being endogenized, as well as human capital. Thediscussion covers the measurement issues and explanation of the role of domestic and foreignR&D expenditures, as well as educational expenditures. The price and wages equations aswell as incomes explaining the expenditures close the model. The discussion is extended toinclude proposals to construct new submodels explaining the sectors of research andeducation and also the ICT industries, as well as the ecological issues.
Argumenta Oeconomica, 2010, Nr 2 (25), s. 5-24
Keywords: technical progress; production functions; R&D expenditures; Knowledge economy; total factor productivity; human capital